Relationship of parenting styles and self-esteem among selected senior high school students - John Patrick G. Tan. 4 0 16; 5 (2017)
ABSTRACT:There are different types of parenting in the world. Some are focused on controlling their child and less on responsiveness. While some are not that controlling but give proper love and care towards their child. A parenting style that a child perceived has a big impact on its character especially to their self-esteem. The purpose of this study is to know the relationship between the types of parenting and self-esteem of a senior high school student in the Pamantasan ng Lungsod ng Maynila. The research is a quantitative type in which the researcher conducted surveys by the use of instruments to measure the type of parenting and self-esteem of the respondents. The data needed to measure the variable were gathered using the two instruments, the Scale of Parenting Style and Rosenberg Self - Esteem. The result obtained by the researcher shown that parenting method that are perceived by the students are no to negligible relationship to the student's self-esteem.
Undergraduate Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2